PENGARUH PERMAINAN LEGO TERHADAP PERKEMBANGAN KREATIVITAS PADA ANAK PRASEKOLAH DI TK B AL MADINAH KABUPATEN JOMBANG: THE EFFECT OF LEGO GAMES ON THE DEVELOPMENT OF CREATIVITY IN PRESCHOOL CHILDREN AT TK B AL MADINAH JOMBANG DISTRICT - Stianto, Mitayakuna; Fatimah, Siti; Rahayu, Yustina (LPPM STIKes Bahrul Ulum Jombang, 2021)
eativity is important to improve children's quality of life, so the development of children's creativity should start as early as possible. Because children's brain development at an early age is included in the golden. children need stimulation through games. of this study was conducted to determine the effect of lego games on the development of creativity. Method: This study used a True Experiment design. The population is class B students at AL Madinah Kindergarten, Jombang Regency as many as 30 students. Samples taken as many as 15 experimental samples and 15 control samples with sampling technique Probability Sampling. by providing pre-post assessments of experimental groups regarding the development of creativity observation sheets. data was using the Wilcoxon Signed Rank Test and Mann-Whitney Test statistical tests. Results: The results showed a value of ρ = 0.001 with α = 0.05 and the value obtained the result of 0.001 < 0.05 (ρ < α) this means that H1 is accepted, namely there is an effect of lego games on the development of creativity in preschool children. Conclusion: there is an effect of lego games on the development of creativity. workers are advised to provide health promotion about games that trigger children's development.